2014
DOI: 10.1039/c4ra09613d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of graphene oxide with human serum albumin and its mechanism

Abstract: We show that GONS inhibit HSA function via two routes: blocking protein active sites, or destroying protein structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…GO has an extremely large specic surface area, rich in oxygen-containing functional groups, which are responsible for its interaction with various proteins without further modication. 15,22 Many studies have addressed the interactions of proteins with GO, and results have shown a problem related to the signicant loss of protein structure and/or activity [23][24][25][26][27][28] due to the electrostatic interaction between the protein functional groups and GO or functionalized GO. On the other hand, in comparison to GO, when reduced graphene oxide (rGO) is used to conjugate proteins, a higher protein loading, higher activity and stability is observed.…”
Section: Introductionmentioning
confidence: 99%
“…GO has an extremely large specic surface area, rich in oxygen-containing functional groups, which are responsible for its interaction with various proteins without further modication. 15,22 Many studies have addressed the interactions of proteins with GO, and results have shown a problem related to the signicant loss of protein structure and/or activity [23][24][25][26][27][28] due to the electrostatic interaction between the protein functional groups and GO or functionalized GO. On the other hand, in comparison to GO, when reduced graphene oxide (rGO) is used to conjugate proteins, a higher protein loading, higher activity and stability is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The GOns-albumax II association might be primarily driven by the hydrophobic interactions between GOns and the hydrophobic regions of albumax II, coupled with electrostatic interactions. [47][48][49] Nonetheless, the GOns concentration-dependent loading capacity of biomolecules on GOns was not observed for both hypoxanthine and gentamicin ( Fig. 3f and g), possibly due to their lower binding association and affinity to GOns.…”
Section: Resultsmentioning
confidence: 93%
“…The interaction of graphene and GO with single proteins has been assessed in terms of binding affinity, action mechanisms, as well as conformational and functional modifications. A recent study considered albumin adsorption to four different types of nanosheets, including pristine GO or GO sheets modified by carboxylic groups (COOH), polyethylenimine (PEI), and chitosan (CS), showing that HSA was readily adsorbed to the GO-based sheets with a higher affinity for pristine GO, followed by COOH-GO, CS-GO, and PEI-GO in that order [196]. From isothermal titration calorimetry analysis, it was concluded that HSA interacted with GO and COOH-GO mainly via hydrogen bonding, while hydrophobic interactions contributed to HSA adsorption to PEI-GO and CS-GO surfaces.…”
Section: Graphene-based Nanostructuresmentioning
confidence: 99%
“…From isothermal titration calorimetry analysis, it was concluded that HSA interacted with GO and COOH-GO mainly via hydrogen bonding, while hydrophobic interactions contributed to HSA adsorption to PEI-GO and CS-GO surfaces. Moreover, the authors suggested that GO affected HSA functionality by blocking the protein active sites or destroying its original structure [196]. Kenry et al investigated the molecular interaction of GO sheets with lateral size distribution in the range between 0.280 µm and 4.138 µm with three of the most abundant human blood plasma proteins, namely HSA, Fng, and γ-IgG.…”
Section: Graphene-based Nanostructuresmentioning
confidence: 99%